Pakistan and Iran Relations A Research on Cultural Dimensions - Arain, Rehana Kausar; Khatti, Deedar Hussain; Keerio, Tarique Hussain (Pakistan Journal of Humanities and Social Sciences, 2025)
Pakistan and Iran disseminate deep-rooted intra-cultural and religious bonds that have especially created bilateral connections since the birth of Pakistan. The influence of Shi'a Islam in Iran and a substantial Shi'a minority in Pakistan anchored in joint Islamic roots, both countries exhibit strong connections in the Muslim world. These bonds are different and improved by a long-standing cultural conversation embedded in the Urdu and Persian languages, literary works, art, and Sufism, which historically linked the territories long before modern borders appeared. Likewise, Persian served as the administrative language in the Indian subcontinent for centuries, having a long-lasting influence on Urdu poetry and intellectual traditions in Pakistan. Similarly, conveyed religious remembrances, such as Ashura, and cultural segments, like Nowruz, are celebrated and respected in both societies. Cultural diplomacy and religious affinity continue to promote people-to-people relations, academic alliances, and regional partnerships. It explores how people-to-people exchanges, cultural festivals, and exchanges contribute to the promotion of reciprocal wisdom and benevolence between these two countries The paper discusses the cultural dimensions creating a bridge of diplomacy and religious roots for regional collaborations between both countries, interpreting the historical growth and modern significance in regional collaborations and identity formation. This paper employs descriptive methods based on secondary data which pivotal for the proposed study. This study aims to shed light on the definite relations through rigorous literature analysis and diving into reliable and authentic sources such as international journals, books, diplomatic reports, national, and international newspapers.